Bigger than a breadbox - Snyder, Laurel (Random House, 2011)
Devastated when her parents separate, twelve-year-old Rebecca must move with her mother from Baltimore to Gran's house in Atlanta, where Rebecca discovers an old breadbox with the power to grant any wish--so long as the wished-for thing fits in the breadbox.